Preparation method of antibacterial and anti-adhesion ultra-high molecular weight polyethylene fiber

The aminoglycoside antibiotics and polysulfonate betaine were modified on the surface of ultra-high molecular weight polyethylene fibers through polyphenol oxidation and autopolymerization, which solved the problem of insufficient antibacterial effect in the prior art, and achieved the long-lasting and efficient antibacterial properties of the fibers. Anti-adhesion improves its performance in surgical suture applications.

CN119465628AActive Publication Date: 2025-02-18MODERN TEXTILE TECH INNOVATION CENT (JIANHU LAB) +1

Patent Information

Application Number
CN202411681781.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing ultra-high molecular weight polyethylene fiber surgical sutures are difficult to achieve long-lasting and efficient antibacterial effects during use, and antibacterial agents are prone to fall off, affecting their application in the surgical site.

Method used

Through polyphenol oxidation and autopolymerization reaction, aminoglycoside antibiotics and polysulfonate betaine are stably modified on the surface of ultra-high molecular weight polyethylene fibers, and the broad-spectrum antibacterial properties of aminoglycoside antibiotics and the hydration of polysulfonate betaine betaine betaine , imparts antibacterial properties and anti-adhesion properties to fibers.

Benefits of technology

It realizes the long-lasting and efficient antibacterial properties of ultra-high molecular weight polyethylene fibers, and improves its application performance in the fields of antibacterial fabrics and biological materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465628A_ABST
    Figure CN119465628A_ABST
Patent Text Reader

Abstract

The invention relates to the field of biomedical materials, and discloses a preparation method and application of an antibacterial and anti-adhesion ultra-high molecular weight polyethylene fiber. According to the preparation method disclosed by the invention, the aminoglycoside antibiotics and the polysulfobetaine are stably modified on the surface of the UHMWPE fiber by utilizing the oxidation self-polymerization reaction of the polyphenol, and the UHMWPE fiber can be endowed with excellent antibacterial property and adhesion resistance by virtue of the broad-spectrum antibacterial property of the aminoglycoside antibiotics and the strong hydration effect of the polysulfobetaine; the application in the fields of antibacterial fabrics, biological materials and the like is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical materials, and in particular to a preparation method and application of antibacterial and anti-adhesive ultra-high molecular weight polyethylene fiber. Background Art

[0002] Surgical site infection is the most common type of hospital-acquired infection and one of the main causes of recurrence and death in patients. Surgical sutures play an important role in wound repair, providing certain support for tissues during the healing period and promoting wound healing. In clinical applications, ideal surgical sutures should meet the conditions of no surface tension, no cytotoxicity and no carcinogenicity, and be able to maintain a sterile environment during the healing process of the wound site. General surgical sutures are only sterilized before use, and the sutures themselves do not have antibacterial ability and cannot resist bacteria produced at the surgical site during the application process. When the wound suture is infected by bacteria, the bacteria will quickly breed and multiply, causing inflammation and swelling of the wound, which not only increases the wound healing time, but also has the risk of secondary surgery. Therefore, antibacterial finishing of surgical sutures can effectively prevent bacterial adhesion and biofilm formation during use, which is of great clinical significance.

[0003] Ultra-high molecular weight polyethylene fiber has excellent mechanical properties. The surgical sutures prepared from it have higher strength, better wear resistance, better operability and knotting safety / strength compared with other fibers, so it is very popular in orthopedic surgery. However, due to the lack of polar groups in its molecular structure, the surface is inert, it is difficult to graft and modify it on the surface, and the coating is difficult to form, so it is very difficult to modify its antibacterial function. The antibacterial effect can be achieved by adsorbing silver nanoparticles, zinc oxide nanoparticles, etc. with antibacterial properties on the surface of ultra-high molecular weight polyethylene through electrostatic or van der Waals forces, but its adsorption force is relatively weak, and the antibacterial agent is easy to fall off, resulting in insufficient durability of the antibacterial effect. The surface of ultra-high molecular weight polyethylene is treated with plasma to produce polar groups on its surface, thereby increasing the surface activity and facilitating subsequent antibacterial modification. However, the cost of plasma treatment equipment is high, and the treatment process requires strict control of parameters, which is difficult to operate. The surface activity after treatment may gradually decrease over time, affecting the durability of the antibacterial effect. Therefore, it is of great significance to develop an ultra-high molecular weight polyethylene suture that can be simply prepared and has durable and efficient antibacterial properties. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing an antibacterial and anti-adhesive ultra-high molecular weight polyethylene fiber and its application. The present invention utilizes the polyphenol oxidation self-polymerization reaction to stably modify aminoglycoside antibiotics and polysulfonated betaine on the surface of UHMWPE fiber at the same time, relying on the broad-spectrum antibacterial property of aminoglycoside antibiotics and the strong hydration of polysulfonated betaine, and can give the ultra-high molecular weight polyethylene fiber excellent antibacterial and anti-adhesive properties, which is beneficial to its application in the fields of antibacterial fabrics, biomaterials, etc.

[0005] The specific technical scheme of the present invention is: a method for preparing an antibacterial and anti-protein adhesion ultra-high molecular weight polyethylene fiber, comprising the following steps:

[0006] 1) Pretreatment: Ultra-high molecular weight polyethylene fiber (UHMWPE fiber) is subjected to ultrasonic treatment and drying to obtain ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0007] 2) Preparation of composite coating: adding polyphenol, aminoglycoside antibiotic and sulfobetaine monomer into water and stirring to dissolve to obtain a mixed solution; placing the ultra-high molecular weight polyethylene fiber described in step (1) into the mixed solution and stirring to react, taking out, washing and drying to obtain antibacterial and anti-protein adhesion ultra-high molecular weight polyethylene fiber.

[0008] The present invention uses a one-step method to modify the surface of UHMWPE fiber using polyphenol compounds, aminoglycoside antibiotics and sulfonated betaine monomers. Among them, antibiotics have a long-lasting and broad-spectrum antibacterial ability, which can give the fiber excellent antibacterial properties, but the surface of UHMWPE fiber is highly inert, and it is difficult to attach antibiotics to its surface by conventional methods. To this end, the present invention has found through research that, compared with other conventional viscous substances, polyphenol compounds have a more excellent adhesion ability to UHMWPE fiber after oxidative self-polymerization, and can firmly adhere to the surface of UHMWPE fiber. On this basis, in order to achieve the attachment of antibiotics, the present invention specifically selects aminoglycoside antibiotics with amino groups. In the process of polyphenol oxidative self-polymerization, a large number of amino groups can participate in the self-polymerization reaction, which helps to accelerate the polymerization of polyphenols, thereby achieving the firm attachment of antibiotics on the surface of UHMWPE fibers. In addition, in the process of polyphenol oxidative self-polymerization, the free radicals generated can induce the polymerization of sulfonated betaine monomers, and then introduce the hydrophilic polymer poly (sulfonated betaine methacrylate) into the coating. The strong hydration effect of polysulfonated betaine can give UHMWPE fiber excellent anti-adhesion to substances such as protein.

[0009] In summary, the present invention ingeniously utilizes the polyphenol oxidation self-polymerization reaction to stably modify aminoglycoside antibiotics and polysulfonated betaine on the surface of UHMWPE fibers at the same time. Relying on the broad-spectrum antibacterial properties of aminoglycoside antibiotics and the strong hydration of polysulfonated betaine, ultra-high molecular weight polyethylene fibers can be endowed with excellent antibacterial and anti-adhesion properties, which is beneficial to their application in the fields of antibacterial fabrics, biomaterials, etc.

[0010] Preferably, in step 2), the mass ratio of polyphenols to aminoglycoside antibiotics in the mixed solution is 1:(0.2-5).

[0011] The Michael addition or Schiff base reaction between polyphenols and aminoglycoside antibiotics plays a decisive role in the formation of the coating, thereby affecting the loading amount of the coating on the surface of the ultra-fiber. First, if the content of polyphenols is too low relative to the aminoglycoside antibiotics, the formed coating is too thin and the reactivity of the fiber surface is low, so that the loading amount of aminoglycoside antibiotics and polysulfonated betaine in the coating may decrease, which will make the antibacterial and anti-adhesion properties of the fiber poor. If the content of polyphenols is too high relative to the aminoglycoside antibiotics, it will cause the polyphenols to self-polymerize in the reaction solution, resulting in precipitation in the reaction solution, and the coating is easy to fall off from the fiber surface. In addition, the antibiotics are expensive, resulting in a significant increase in costs, which is not conducive to the marketization of antibacterial ultra-high molecular weight polyethylene fibers, and may also cause bacterial resistance.

[0012] Preferably, in step 2), the concentration of the sulfobetaine monomer in the mixed solution is 0.0125-0.075 mol / L.

[0013] The chemical structure of sulfobetaine monomers contains a quaternary ammonium salt cation center and a sulfonate anion, which are close to each other in the molecule to form an "inner salt" structure. This structure makes sulfobetaine monomers have the characteristics of zwitterions, and can maintain a certain charge balance under different pH environments. Because of its surface activity and anti-protein adsorption characteristics, the introduction of sulfobetaine monomers into the preparation of material surface coatings can effectively reduce the adhesion of dirt and biomacromolecules on the surface of materials, thereby improving the anti-fouling performance of materials. However, when the concentration of sulfobetaine monomers is too high, there are too many solutes in the reaction system, and a certain amount of polyphenols and aminoglycoside antibiotics have limited initiation effects on the monomers, so that the content of polysulfobetaine in the surface components of the generated coating is too low, and its anti-adhesion and anti-fouling properties cannot be fully and effectively utilized; when the concentration of sulfobetaine monomers is too low, the polymerization of sulfobetaine is completed but the content is too low, and the purpose of anti-adhesion and anti-fouling cannot be achieved.

[0014] Preferably, in step 2), the reaction temperature is 25-37° C. and the reaction time is 18-24 h.

[0015] The reaction time affects the thickness of the coating and the number of active groups. If the reaction time is too short, the coating formed by polyphenols and aminoglycoside antibiotics is too thin, too few active groups are introduced to the fiber surface, and the antibacterial activity of the fiber is greatly reduced. However, too long a reaction time cannot further improve the performance of the coating.

[0016] Preferably, in step 2), the polyphenol is selected from at least one of dopamine, tannic acid and catechol.

[0017] Preferably, in step 2), the aminoglycoside antibiotic is at least one selected from streptomycin, gentamicin, kanamycin, amikacin and tobramycin.

[0018] Preferably, in step 2), the sulfonate betaine monomer is selected from sulfonate betaine methacrylate, dodecyl sulfonate betaine, 3-(sulfopropyl) methacrylamide, p-styrene sulfonate betaine and the like.

[0019] Preferably, in step 2), the ratio of the ultra-high molecular weight polyethylene fiber to the mixed solution is 0.05-0.1 g / mL.

[0020] Preferably, in step 1), the ultrasonic treatment is carried out in a mixed solution of ethanol and acetone; further preferably, the volume ratio of ethanol to acetone is 1:(0.5-1).

[0021] UHMWPE fibers may be attached with some impurities during daily storage, which may affect the subsequent chemical modification process. In order to effectively remove impurities such as solid particles on the fiber surface, it is immersed in a mixed solution of ethanol and acetone in a certain volume ratio for ultrasonic treatment.

[0022] Preferably, in step 1), the ultrasonic treatment time is 60-120 min; and the drying temperature is 40-70°C.

[0023] Ultrasonic time has an important influence on the removal effect of impurities. If the ultrasonic time is too short, impurities will remain, which is not conducive to the stable combination of the coating on the fiber surface. In order to speed up the volatilization of the solvent on the fiber surface, the fiber needs to be dried. If the drying temperature is too high, the fiber may creep, causing fiber aging and reducing its service life. If the drying temperature is too low, ethanol and acetone may remain on the fiber surface.

[0024] Preferably, in step 2), the drying temperature is 40-70°C.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] (1) The present invention utilizes the polyphenol oxidation self-polymerization reaction to stably modify aminoglycoside antibiotics and polybetaine sulfonate on the surface of UHMWPE fibers at the same time, relying on the broad-spectrum antibacterial activity of aminoglycoside antibiotics and the strong hydration effect of polybetaine sulfonate, to give ultra-high molecular weight polyethylene sutures excellent antibacterial and anti-adhesion properties.

[0027] (2) The method of the present invention has simple process and low cost, and is suitable for industrial promotion. The coating obtained by the method of the present invention has good uniformity and strong bonding force, which ensures the quality and stability of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Optical images of the reaction solution and fiber used in the multifunctional modification of the fiber in Examples 1-4;

[0029] Figure 2 The SEM photos of the fibers after multifunctional modification in Examples 1-4 are shown;

[0030] Figure 3 The knotless breaking strength and knotted breaking strength of Example 1 and Comparative Example 3;

[0031] Figure 4 The antibacterial results of Example 1 and Comparative Example 3 are shown;

[0032] Figure 5 AFM images of Example 1 and Comparative Example 3;

[0033] Figure 6 2 is a fluorescence intensity diagram of Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Example 1

[0036] (1) Pretreatment of ultra-high molecular weight polyethylene suture fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0037] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.04 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0038] Example 2

[0039] (1) Pretreatment of ultra-high molecular weight polyethylene suture fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 100 min. The fiber was taken out and washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0040] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.04 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain catechol-tobramycin / sulfobetaine methacrylate modified ultra-high molecular weight polyethylene suture fiber.

[0041] Example 3

[0042] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0043] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.08 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0044] Example 4

[0045] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0046] (2) Preparation of catechol-tobramycin / betaine methacrylate composite coating: 0.08 g of catechol, 0.04 g of tobramycin and 0.0125 mol / L of betaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain catechol-tobramycin / betaine methacrylate modified ultra-high molecular weight polyethylene suture fiber.

[0047] Comparative Example 1

[0048] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0049] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.4 g of catechol, 0.04 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0050] Comparative Example 2

[0051] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0052] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.4 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0053] Comparative Example 3

[0054] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0055] (2) Preparation of catechol-tobramycin composite coating: 0.04 g of catechol and 0.4 g of tobramycin were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain catechol-tobramycin modified ultra-high molecular weight polyethylene suture fiber.

[0056] Comparative Example 4

[0057] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0058] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.04 g of tobramycin and 0.00625 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0059] Comparative Example 5

[0060] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0061] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.04 g of tobramycin and 0.075 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0062] Comparative Example 6

[0063] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0064] (2) Preparation of catechol-tobramycin / sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.04 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 4 h, then washed with water and dried at 40° C. to obtain an ultra-high molecular weight polyethylene suture fiber modified with catechol-tobramycin / sulfobetaine methacrylate.

[0065] Comparative Example 7

[0066] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0067] (2) Preparation of catechol-tobramycin sulfobetaine methacrylate composite coating: 0.04 g of catechol, 0.04 g of tobramycin and 0.0125 mol / L of sulfobetaine methacrylate were added to 20 mL of deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 40 h, then washed with water and dried at 40° C. to obtain catechol-tobramycin / sulfobetaine methacrylate modified ultra-high molecular weight polyethylene suture fiber.

[0068] Comparative Example 8

[0069] (1) Pretreatment of ultra-high molecular weight polyethylene fiber: The ultra-high molecular weight polyethylene fiber was placed in a mixed solution of ethanol and acetone in a volume ratio of 1:1 and ultrasonicated for 60 minutes. After being taken out, the fiber was washed with water and dried at 40°C to obtain an ultra-high molecular weight polyethylene fiber with no impurities on the surface.

[0070] (2) Preparation of tannic acid-gentamicin / sulfobetaine methacrylate composite coating: 0.04 g tannic acid, 0.04 g gentamicin and 0.0125 mol / L sulfobetaine methacrylate were added into 20 ml deionized water and stirred thoroughly until dissolved. The ultra-high molecular weight polyethylene fiber obtained in step (1) was placed in the solution at 0.075 g / mL and stirred at 25° C. for 24 h, then washed with water and dried at 40° C. to obtain ultra-high molecular weight polyethylene suture fiber modified with tannic acid-gentamicin / sulfobetaine methacrylate.

[0071] Performance Testing

[0072] The materials in each embodiment and comparative example were tested. The surface morphology of the suture fiber was observed by scanning electron microscopy (SEM), the surface chemical elements were tested by EDS, the roughness was tested by atomic force microscopy (AFM), and the specific test methods for antibacterial properties, cytotoxicity, tensile behavior and bending behavior were as follows:

[0073] Antibacterial performance test: The antibacterial performance of fiber samples was tested according to the GB / T20944.3-2008 oscillation method. 67.5 cm long fiber samples were mixed with 3 mL of bacterial solution (10 6 CFU / mL) were co-cultured at 25°C and 150 r / min for 18 h. The bacterial solution was diluted and plated, and the antibacterial rate was calculated based on the number of colonies.

[0074] Cytotoxicity test: The sterilized ultra-high molecular weight polyethylene fiber was placed in a 96-well plate containing a 3T3 cell suspension (200 μL / well, 5000 cells / well) and incubated for 24 hours. The culture medium was aspirated, and CCK-8 solution was added to each well and incubated for another 3 hours. The absorbance at 450 nm was measured using a microplate reader (PerkinElmer), and three independent experiments were performed. The cell survival rate was calculated using the cell survival rate formula. If the cell survival rate is greater than 80%, the dressing is considered to be non-cytotoxic.

[0075] Cell survival rate (%) = [(A s -A b )-(A c -A b )]×100%

[0076] Among them: A s : Absorbance of experimental group, A c : Absorbance of control group, A b : Absorbance of blank group.

[0077] Anti-adhesion performance test: bovine serum albumin (BSA) was used as a model protein to determine the protein adsorption of the suture. For quantitative evaluation, the samples were loaded into a well plate with 1 mL of FITC-BSA solution (1 mg / ml), incubated at 37°C for 4 h, and then observed and photographed with a laser confocal microscope, and the corresponding fluorescence intensity was measured with Image J.

[0078] Tensile behavior: The tensile properties of the sutures were tested using a YG026Q fabric strength tester (Ningbo Textile Instrument Factory, Ningbo, Zhejiang Province). The suture tensile performance gauge length was 125 mm, the tensile speed was 300 mm min-1, and then the sutures were stretched, and the tensile curve, breaking strength and breaking elongation were recorded. Each sample was tested 5 times. The tensile properties of the knotted sutures were also tested.

[0079] Bending behavior: Bending stiffness (B) was measured by the cantilever method and calculated according to formula (1). Briefly, a suture with a length of 5 cm was placed horizontally, and one end of the connecting force (F = 2.5 × 10-3 N) was suspended 1 cm (L) in the air. After loading for 15 seconds, the vertical distance (X) between the horizontal plane and the loading end was measured, and each sample was repeated 5 times.

[0080]

[0081] where B, F, L, and X represent the bending stiffness, the force applied to the suture, the length of the suspended suture, and the deflection of the suture, respectively.

[0082] The test results are shown in the following table and Figure 1-6 As shown:

[0083]

[0084]

[0085] In the above table, the S element content is used to indirectly characterize the SBMA content on the modified fiber surface; the antibacterial rate reflects the antibacterial properties of ultra-high molecular weight polyethylene surgical suture fibers; the cell viability characterizes the biocompatibility and cytotoxicity of the antibacterial surgical sutures; the fluorescence intensity characterizes the anti-adhesion properties of the antibacterial surgical sutures; the tensile breaking strength, knotted tensile breaking strength and bending stiffness characterize the mechanical properties and operability indicators of the antibacterial surgical sutures.

[0086] From the table and Figure 1-6 The results show that the ultra-high molecular weight polyethylene suture fiber can be successfully prepared with antibacterial and anti-adhesion properties by using the Michael addition or Schiff base reaction between polyphenols and aminoglycoside antibiotics to modify the coating of the ultra-high molecular weight polyethylene suture fiber and initiating the polymerization of sulfobetaine on the surface of the suture fiber (Examples 1-4). In addition, the selection of some process conditions in the preparation process is critical, as follows:

[0087] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the concentration of catechol in the reaction solution is much greater than the concentration of tobramycin. The results show that when the tobramycin content is relatively low relative to the catechol content, the antibacterial rate of the antibacterial surgical suture is greatly reduced. This is because the high content of catechol causes its self-polymerization in the reaction system to dominate the reaction. The main component of the coating loaded on the fiber surface is polycatechol, and the tobramycin content is extremely low, which reduces the antibacterial ability of the coating components.

[0088] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the concentration of catechol in the reaction solution is much lower than that of tobramycin. The results show that when the tobramycin content is too high relative to the catechol content, although the presence of tobramycin can promote the acceleration of the polymerization of catechol, the content of catechol is too low, so although the polymerization promoting effect is very strong, the content of catechol itself is too low, so the coating formed on the fiber surface is not obvious. At the same time, the polymerization of sulfobetaine also requires hydroxyl radicals generated by catechol, so the S element content in the coating is also low.

[0089] Comparative Example 3: In the preparation method of Comparative Example 3, sulfobetaine methacrylate (S content is 0) is not introduced. Figure 5 As shown, it was finally found that the composite coating formed on the fiber surface was relatively rough and uneven, which may cause secondary damage to the wound during surgical suturing and greatly reduce the anti-adhesion property of the suture fiber.

[0090] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that the concentration of the sulfonate betaine methacrylate monomer is different. The concentration of the sulfonate betaine methacrylate in Comparative Example 4 is 0.00625 mol / L. The results show that when the concentration of the sulfonate betaine methacrylate monomer is too low, the content of the corresponding S element in the composite coating formed on the fiber surface decreases. At this time, there are sufficient hydroxyl radicals to initiate the polymerization of the sulfonate betaine methacrylate, but the amount of the sulfonate betaine methacrylate itself is insufficient to form a uniform coating on the fiber surface.

[0091] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that the concentration of sulfonate betaine methacrylate monomer is different. The concentration of sulfonate betaine methacrylate in Comparative Example 5 is 0.075 mol / L. The results show that when the concentration of sulfonate betaine methacrylate monomer is too high, the content of S element in the composite coating formed on the fiber surface is not increased. This may be because the reactivity of catechol and tobramycin is certain, resulting in excessive sulfonate betaine methacrylate monomer cannot be fully initiated, and the performance of the composite coating is not improved, resulting in waste.

[0092] Comparative Example 6-7: The difference between Comparative Example 6-7 and Example 1 is that the functional modification time is different. The results show that if the functional modification time is too short (Comparative Example 6), the coating formation time is too short, and the reaction does not occur completely, resulting in the fiber surface coating being too thin, making the suture fiber antibacterial and anti-adhesion functions poor. On the contrary, if the functional modification time is too long (Comparative Example 7), the reaction reaches saturation, the coating load does not increase significantly, and the reaction time is too long, resulting in too low efficiency and no significant improvement in function.

[0093] Comparative Example 8: The difference between Comparative Example 8 and Example 1 is that the polyphenol used is tannic acid, and the aminoglycoside antibiotic used is gentamicin sulfate. The results show that changing the types of polyphenols and antibiotics used does not affect their antibacterial and anti-adhesion properties. It is proved that the method provided by the present invention is a feasible method for preparing an antibacterial and anti-adhesion surgical suture coating by combining polyphenols, aminoglycoside antibiotics and sulfobetaine SBMA.

[0094] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing antibacterial and anti-adhesive ultra-high molecular weight polyethylene, characterized in that The following steps are involved: 1) Pretreatment: Ultra-high molecular weight polyethylene fibers are subjected to ultrasonic treatment and drying to obtain ultra-high molecular weight polyethylene fibers with no impurities on the surface; 2) Preparation of composite coating: adding polyphenol, aminoglycoside antibiotic and sulfobetaine monomer into water and stirring to dissolve to obtain a mixed solution; placing the ultra-high molecular weight polyethylene fiber in step (1) into the mixed solution and stirring to react, taking out, washing and drying to obtain an antibacterial and anti-protein adhesion ultra-high molecular weight polyethylene fiber; The mass ratio of polyphenols to aminoglycoside antibiotics in the mixed solution is 1:(0.2-5); The concentration of the sulfobetaine monomer in the mixed solution is 0.0125-0.075 mol / L.

2. The preparation method according to claim 1, characterized in that: In step 1), the ultrasonic treatment is carried out in a mixed solution of ethanol and acetone.

3. The preparation method according to claim 2, characterized in that: In step 1), the volume ratio of ethanol to acetone in the mixed solution is 1:(0.5-1).

4. The preparation method according to claim 1, characterized in that: In step 1), The ultrasonic treatment time is 60-120 min; The drying temperature is 40-70°C.

5. The preparation method according to claim 1, characterized in that: In step 2), the polyphenol is selected from at least one of dopamine, tannic acid and catechol.

6. The preparation method according to claim 1, characterized in that: In step 2), the aminoglycoside antibiotic is at least one of streptomycin, gentamicin, kanamycin, amikacin and tobramycin.

7. The preparation method according to claim 1, characterized in that: In step 2), The sulfobetaine monomer is selected from dodecyl sulfobetaine, 3-(sulfopropyl)methacrylamide, and p-styrene sulfobetaine; The dosage ratio of the ultra-high molecular weight polyethylene fiber to the mixed solution is 0.05-0.1 g / mL.

8. The preparation method according to claim 1, characterized in that: In step 2), the reaction temperature is 25-37° C. and the reaction time is 18-24 h.

9. The preparation method according to claim 1, characterized in that: In step 2), the drying temperature is 40-70°C.

10. Use of the antibacterial and anti-adhesion ultra-high molecular weight polyethylene fiber prepared according to the preparation method of any one of claims 1 to 9 in the preparation of surgical sutures.

Citation Information

Patent Citations

  • Polydopamine-based biofunction modification method

    CN102000658A

  • Mussel-adhered and cytomembrane antifouling double-bionic multi-armed PEG and preparation method thereof

    CN104804195A

  • Functional modification method for surface and interface of material based on polyphenol compounds

    CN105218847A

  • Anti-infection soft tissue medical adhesive and preparation method thereof

    CN105251038A

  • Biomaterial modified with hydrophilic lubrication coating on surface and preparation method of biomaterial

    CN109912826A

Cited By

  • Intelligent color-changing absorbable suture line and preparation method thereof

    CN121102547A

  • Intelligent color-changing absorbable suture and method of making same

    CN121102547B